Keynote address - Labassiere, Dennis (Dominica Association of Industry & Commerce RoseauDM, 1993)
Notes the political changes in Eastern Europe and the effect on the Caribbean of the establishment of large trading blocs. Opines that a healthy and vibrant private sector is necessary for meaningful economic growth.